Survey of Nematode-Destroying Fungi from Selected Vegetable-Growing Areas in Kenya - P M Wachira (Society for Promotion of Horticulture - Indian Institute of Horticultural Research, 2015)
Plant-parasitic nematodes cause severe damage to a wide range of economic crops, causing upto 5% yield losses globally. In Kenya, vegetables are affected, among other pests, by parasitic nematodes, causing upto 80% loss in yield. Nematode control is very difficult and relies heavily on use of chemical nematicides. Use of these chemical nematicides leads to biological magnification, and elimination of natural enemies of other pathogens, thus creating a need for greater application of pesticides, increased production costs, and development of insecticide-resistance. These factors have led to a growing interest in search for alternate management strategies. The objective of this study was, therefore, to document nematode-destroying fungi in selected, major vegetable-growing areas in Kenya as a step towards developing a self-sustaining system for management of plant-parasitic nematodes. Soil samples were collected from five vegetable-production zones, viz., Kinare, Kabete, Athi-river, Machakos and Kibwezi, and transported to the laboratory for extraction of nematode-destroying fungi. The soil-sprinkle technique described by Jaffee et al (1996) was used for isolating the nematode-destroying fungi from soil, while, their identification was done using identification keys described by Soto Barrientos et al (2001). From this study, a total of 171 fungal isolates were identified as nematodedestroying. The highest population was recorded in Kabete, at 33.9% of the total, followed by Machakos, Kibwezi, Athi-river, with the least in Kinare, at 24.6, 22.2, 11.7 and 7.6% of the total population, in that order. Arthrobotrys was the most frequent genus, with mean occurrence of 7.3, followed by Monacrosporium with 6 and Stylophage with 5.2. A. dactyloides was significantly (P=0.002) affected by the agro-ecological zone, with the highest occurrence recorded in Kabete, and the least in Athi-river. Kibwezi recorded highest diversity index, with a mean of 1.017, while, Athi-river recorded the least, with a mean of 0.333. Kibwezi had the highest species richness, recording a mean of 3.4, while, the least mean of 1.6 was recorded in Athi-river. Mean species richness of 2.2 was recorded for both Kabete and Machakos, and 1.8 for Kinare. From the three genera recorded, Arthrobotrys was more effective at trapping nematodes compared to Monocrosporium and Stylopage. The genus Arthrobotrys had the highest number of trapped nematodes, with a total population of 57, followed by Monacrosporium, the least being Stylopage, with 45 and 36, respectively, in a period of 104 hours. From the study, it is evident that agricultural practices affect occurrence and diversity of nematodedestroying fungi, and, Arthrobotrys can be used as a bio-control agent for managing plant-parasitic nematodes.